2020
DOI: 10.33314/jnhrc.v17i4.2187
|View full text |Cite
|
Sign up to set email alerts
|

Sex Predictability by Using Mandibular Canine Index

Abstract: Background: Canines are known for their higher resistance to trauma and pathological alterations when compared to other teeth. Among all the teeth, canines show highest sexual dimorphism.Methods: This descriptive cross-sectional study was commenced from January 2019 to April 2019 after the ethical approval from Institutional Review Committee. The maximum mesio-distal widths of right and left mandibular canines and mandibular inter-canine arch width were measured on the cast with the help of a divider and digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…39,40 However, when other authors tested the validity and applicability of the MCI in more diverse populations, they found much lower accuracy rates compared to the original authors. 41,42 Silva et al found low accuracy classification rates (54.2%) in using the MCI for sex estimation in their study of 120 subjects from a Portuguese sample, 41 while Atreya et al also reported lower accuracy rates (57.5-62.5%) of using the MCI for sex estimation in their study of 80 subjects from a Nepalese population. 42 Both groups of authors proposed for more population-specific studies and cautioned the application of the MCI in their ethnic populations for sex estimation.…”
Section: Incisor Index and Mandibular Canine Indexmentioning
confidence: 93%
See 1 more Smart Citation
“…39,40 However, when other authors tested the validity and applicability of the MCI in more diverse populations, they found much lower accuracy rates compared to the original authors. 41,42 Silva et al found low accuracy classification rates (54.2%) in using the MCI for sex estimation in their study of 120 subjects from a Portuguese sample, 41 while Atreya et al also reported lower accuracy rates (57.5-62.5%) of using the MCI for sex estimation in their study of 80 subjects from a Nepalese population. 42 Both groups of authors proposed for more population-specific studies and cautioned the application of the MCI in their ethnic populations for sex estimation.…”
Section: Incisor Index and Mandibular Canine Indexmentioning
confidence: 93%
“…41,42 Silva et al found low accuracy classification rates (54.2%) in using the MCI for sex estimation in their study of 120 subjects from a Portuguese sample, 41 while Atreya et al also reported lower accuracy rates (57.5-62.5%) of using the MCI for sex estimation in their study of 80 subjects from a Nepalese population. 42 Both groups of authors proposed for more population-specific studies and cautioned the application of the MCI in their ethnic populations for sex estimation. 41,42 Variations in tooth size and arch width size could vary amongst different populations, which would affect the MCI and render it less accurate for sex estimation.…”
Section: Incisor Index and Mandibular Canine Indexmentioning
confidence: 93%
“…The accuracy of the sex estimation by MCI was verified and, despite varying among studies, the minimum and maximum values found were, respectively, 20% (Anu et al 2018) and 87.5% (Rao et al 1989) for women and 40.6% (Jacob et al 2018) and 94% (Silva et al 2016) for men. The results found led some studies (Acharya et al 2011;Acharya and Mainali 2009;Atreya et al 2019;Gargano et al 2014;Hosmani et al 2013) to the conclusion that the canine mandibular index is not reliable for sex estimation, while others (Bakkannavar et al 2015;Dhakar et al 2012;Divyadharsini and Kumar 2019;Kaushal et al 2004;Kumawat et al 2017) guaranteed the applicability of this index in forensic practice.…”
Section: Resultsmentioning
confidence: 99%
“…The samples of the selected studies involved the population of some countries in Asia, Africa, Europe, and America, with the Indians being the most investigated (n = 37), and the sample size varied between 50 (Krishnan et al 2016;Muthukumar and Thenmozhi 2018) and 1000 (Gargano et al 2014;Jacob et al 2018) participants. The youngest individuals analyzed were 14 years old (Dhakar et al 2012;Duraiswamy et al 2009;Sherfudhin et al 1996); the most advanced age examined was 60 years old (Gargano et al 2014;Sassi et al 2012) and some studies (Atreya et al 2019;Muhamedagić and Sarajlić 2013;Muller et al 2001) did not inform the studied age group. Most of the selected studies analyzed only the right and left mandibular canines.…”
Section: Resultsmentioning
confidence: 99%
“…Buccolingual distance was recorded as the greatest distance between the buccal and lingual surfaces of the crown [ 12 ]. Intercanine distance was measured between the tips of the maxillary canines [ 13 ].…”
Section: Methodsmentioning
confidence: 99%